Higher education in the world 3 (Palgrave Macmillan, 2008)
This annual report explores in depth the key issues facing Higher Education institutions in the Twenty-first century including perspectives from the five continents, with special emphasis on the theme of the social commitment of universities. It includes papers from eminent scholars, a Delphi poll from over 70 key experts/practitioners on the subject of creating a knowledge society, and extensive supporting statistics and analytical maps. Its publication coincides with the annual International Barcelona Conference on Higher Education